Management Strategy for the Development of Pesantren's Hidden Curriculum in Schools - Carnawi, Carnawi; Zamzami, Zamzami; Nasoha, Ahmad Muhamad Mustain; Muarif, Yahya Zaenul; Abdullah, Imam (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The curriculum at SMPIQu Al-Bahjah Cirebon faces a challenge in integrating the formal, official curriculum with the non-formal pesantren (Islamic boarding school) curriculum. This disconnect has resulted in the pesantren curriculum becoming somewhat